Biomotor profile of primary school students in East Java - Ihwanul Muslimin; Prisca Widiawati; Supriatna; Muhammad Putra Ramadhan (Indonesian Journal of Sport Management, 2025)
Improving biomotor capacity is crucial due to the increasing demands for physical activity in daily life. This study aims to evaluate the status of biomotor abilities among elementary school students in grades IV, V, and VI in East Java. The research employs a descriptive quantitative approach using a survey method. Data were collected through various tests and measurements. The population consisted of 1,438 students, both male and female, from 10 elementary schools distributed across East Java Province. Data analysis was conducted using quantitative descriptive methods, focusing on percentage calculations. The findings reveal that the biomotor component of eye-hand coordination among male students scored 41%, while female students scored 46%, both categorized as “moderate.” In terms of arm muscle strength, male students achieved a score of 32% and female students 36%, placing them in the “less” category. The leg muscle power component scored 57% for both genders, also falling within the “moderate” category. Agility scores indicated that male students achieved 59% and female students 60%, categorized as “moderate” and “good,” respectively. Speed scores showed males at 47% and females at 48%, both in the “moderate” category. Lastly, cardiovascular endurance scores were 45% for boys and 48% for girls, again categorized as “moderate.” Overall, the analysis indicates that the biomotor components of elementary school students in grades IV, V, and VI in East Java are primarily in the “moderate” category, highlighting areas for potential improvement in physical education programs.